Різальний композит кубічного нітриду бору з низькомодульною добавкою жароміцного нітриду кремнію - Петруша, І.А.; Осіпов, О.С.; Смірнова, Т.І.; Муковоз, Ю.О.; Дуб, С.М.; Нікішина, М.В.; Суліма, О.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Cubic BN/Si₃N₄ ceramic composite of the different Si₃N₄ contents was fabricated at high pressure (8 GPa) and its physical properties of density, bulk modulus, strength, hardness, fracture toughness and thermal conductivity were evaluated to examine the potential of these ceramics as wear-resistant tool material. cBN/(3–10) mas. % Si₃N₄ phase combinations result in a composite with superior mechanical properties to those commercially available.